2013
DOI: 10.1007/s11999-013-2908-8
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Effects of Bone and Soft Tissue Injury on Systemic Inflammation: A Pilot Study

Abstract: Background In multiply injured patients, bilateral femur fractures invoke a substantial systemic inflammatory impact and remote organ dysfunction. However, it is unclear whether isolated bone or soft tissue injury contributes to the systemic inflammatory response and organ injury after fracture. Questions/purposes We therefore asked whether the systemic inflammatory response and remote organ dysfunction are attributable to the bone fragment injection, adjacent soft tissue injury, or both. Methods Male C57/BL6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…As a biomedical explanation of the influence of fracture instability on mortality, we favor the preliminary evidence linking bone fracture fragments and consequent soft tissue injury to the initiation of a systemic inflammatory process likely related to pro-and anti- inflammatory cytokine responses at the time of injury. 20 There are adverse consequences of systemic inflammation in older immunocompromised or respiratory compromised patients. Furthermore, Vester et al 21 also report that the inflammatory response may also be dysregulated in older patients with hip fracture when compared with younger patients with long bone fracture.…”
Section: Discussionmentioning
confidence: 99%
“…As a biomedical explanation of the influence of fracture instability on mortality, we favor the preliminary evidence linking bone fracture fragments and consequent soft tissue injury to the initiation of a systemic inflammatory process likely related to pro-and anti- inflammatory cytokine responses at the time of injury. 20 There are adverse consequences of systemic inflammation in older immunocompromised or respiratory compromised patients. Furthermore, Vester et al 21 also report that the inflammatory response may also be dysregulated in older patients with hip fracture when compared with younger patients with long bone fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that after resuscitation the local microcirculation disturbance appears to last for a longer period . This might be due to the post‐traumatic local and systemic increase of inflammation mediators, such as IL‐6 (Interleukin), IL‐8, IL‐10, HMGB 1 (High mobility group box 1) and TNF‐a (tumor necrosis factor alpha) . These mediators may affect the local perfusion by influencing the tone of the vessels and metabolism of the local tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic injuries initiate a systemic inflammatory response that can lead to tissue adaptation at sites not directly affected by the initial injury (11,12) . In bone, it is well established that the bone formation and bone resorption rates near a fracture are higher than baseline activity; this is known as regional acceleratory phenomenon (RAP) (13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%